The Consequences of Chaos Syria's Humanitarian Crisis and the Failure to Protect - Ferris, Elizabeth (The Marshall Papers, 2016)
The Syrian displacement crisis raises fundamental questions about the relationship between action to resolve conflicts and humanitarian aid to assist the victims and demonstrates the limits of humanitarian response, even on a massive scale, to resolve political crises. The increasingly protracted nature of the crisis also raises the need for the international community to think beyond just relief assistance and adopt developmental policies to help refugees become productive members of their host communities. The Consequences of Chaos looks beyond the ever-increasing numbers of Syria's uprooted population to consider the long-term economic, political, and social implications of this massive movement of people.